Performance Assessment of RCC-Steel Hybrid Structure - Bhatt, Lalit; Kunwar, Gokarna; Ojha, Manas Raj; Chaulagain, Milan; Koirala, Nabin; Rijal, Ozone; Poudel, Pradhyumna (Journal of Engineering Issues and Solutions, 2025)
This study presents a comparative evaluation of the seismic performance of three structural systems: Reinforced Cement Concrete (RCC), structural steel, and a vertically mixed RCC and steel hybrid frame. In the hybrid configuration, RCC is used in the lower two storeys and structural steel in the upper two, aiming to combine the strengths of both materials—concrete for its mass and stiffness, and steel for its lightness and ductility. Three building models of G+4 storeys each were developed in FEM tool ETABS and analyzed using the Equivalent Static Method, the Response Spectrum Method, and nonlinear Pushover Analysis in accordance with NBC 105:2020. Key performance parameters such as base shear, storey displacement, inter-storey drift, and pushover capacity were studied. The RCC model showed the highest base shear due to its heavier mass, while the steel structure exhibited better ductility and lower displacement but required larger sections and bracings to maintain structural stiffness. Steel model experienced 30% less base shear while RCC-Steel Hybrid Model experienced 17% less base shear compared to RCC model. The hybrid model exhibited drift and displacement responses that were intermediate to those of the RCC and steel structures. The hybrid model achieved a balanced performance, providing rigidity at the base and flexibility at the upper levels. The spectral acceleration value at performance point was highest for hybrid model (0.74g) compared to for RCC and Steel models (0.666g for both). Pushover analysis confirmed that the hybrid structure remained within acceptable life safety performance limits with no non-linear hinges formed at performance point indicating better seismic resilience than RCC and steel models. These findings suggest that RCC and steel hybrid systems offer a practical and efficient alternative for mid-rise construction, especially in regions like Nepal where staged construction is common, resources may be limited and high seismicity is found.